The Influence of Stock Ownership on Company Performance Listed Food and Drink on the Indonesian Stock Exchange Period 2020-2022 - Desak Putu Setiti Nurani; Ni Wayan Suartini; I Nyoman Gede Supraptha (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This research aims to determine managerial ownership, institutional ownership and public ownership of the performance of food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. This research is a type of quantitative descriptive research. The population in this research is food and beverage companies listed on the Indonesia Stock Exchange (BEI) from 2020-2022, totaling 33 companies. Determining the sample in this study used a saturated sampling technique, that is, the entire population was sampled. This research technique uses multiple linear regression analysis techniques. By testing the hypothesis with the T test, Determination test and F test. The results of the research show that (1) Managerial Ownership has a positive and insignificant effect on company performance as proven by the Sig Sig value. 0.348 ≥ 0.05, (2) Institutional ownership has a positive and insignificant effect on company performance as evidenced by a Sig value of 0.003 ≤ 0.05, (3) Public ownership has a positive and insignificant effect on company performance as evidenced by a Sig value of 0.989≥ 0 .05. Managerial Ownership, Institutional Ownership and Public Ownership simultaneously have no effect on company performance as evidenced by the Sig value of 0.294 ≥ 0.05. The suggestion for further research is that it is hoped that it will be able to develop better research in the future regarding improving company performance and adding research variables.